Modified Valsalva maneuver after burr-hole drainage of chronic subdural hematomas: A single-center cohort study - Zeng, Lang; Yu, Jiasheng; Chen, Rudong; Yang, Hongkuan; Li, Hua; Zeng, Lingcheng; Wang, Junhong; Xu, Weidong; Hu, Shengqi; Chen, Kun (Frontiers in Neurology, 2023)
Background: Previous studies of chronic subdural hematoma (cSDH) management mainly involve potential postoperative recurrence and safety precaution. In this study, a non-invasive postoperative treatment method involving modified Valsalva maneuver (MVM), which could reduce the SDH recurrence, is proposed for cSDH. This study aims to clarify the influences of MVM on functional outcomes and recurrence rates of cSDH. Methods: A prospective study was conducted in our institution (Department of Neurosurgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology) during November 2016 - December 2020. 285 adult patients surgically treated by burr-hole drainage of cSDH with subdural drains embedded were enrolled and divided into MVM group (n=117) and control (HC) group (n=98). For MVM, the patients were exposed to a customized MVM device for at least 10 times per hour, 12 hours per day. Herein, the recurrence rate of SDH was employed as the primary endpoint, while functional outcomes and morbidity three months after the surgery were employed as the secondary outcomes. Results: 9 out of 117 patients (7.7%) in the MVM group were exposed to SDH recurrence, while 19 out of 98 patients (19.4%, p0.05) in the HC group were exposed to SDH recurrence. Meanwhile, the infection rate of diseases such as pneumonia in the MVM group (1.7%) was significantly reduced compared with the HC group (9.2%, p<0.001, odds ratio (OR) 0.1). Three months after the surgery, 109 out of 117 patients (93.2%) in the MVM group achieved a favorable prognosis, compared to 80 out of 98 patients (81.6%) in the HC group (p=0.008, with OR of 2.9). Additionally, infection rate (with OR of 0.2) and age (with OR of 0.9) are independent predictors of favorable prognosis at the follow-up stage. Conclusions: The proposed MVM shows good safety and effectiveness in the postoperative management of cSDHs, resulting in reduced recurrence and infection rates of cSDHs after burr-hole drainage, thus achieving a favorable prognosis at the follow-up stage.